Biological applications of phytosynthesized gold nanoparticles using leaf extract of Dracocephalum kotschyi. Issue 3 (6th December 2018) - Chahardoli, Azam; Karimi, Naser; Fattahi, Ali; Salimikia, Iraj
Abstract: In this work, biosynthesis potentials of Dracocephalum kotschyi leaf extract for the production of gold nanoparticle (AuNPs) were studied, and the biological (catalytic, antibacterial, antioxidant, and anticancer) activities of studied AuNPs were evaluated. Different analytical techniques including UV–visible spectroscopy, X‐ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), energy dispersive X‐ray analysis, and transmission electron microscopy (TEM) were used for the characterization of AuNPs. Moreover, Different testing methods were used for evaluating biological activities of biosynthesized AuNPs. The formation of AuNPs was confirmed by color change and UV–visible spectroscopic analysis. Field emission (FE)‐SEM and TEM images were used to characterize phytosynthesized AuNPs which were predominantly spherical in shape with size in the range of 5–21 nm. These spherical NPs were found to be 39.79 ± 5 nm in size as determined by dynamic light scattering particle size analyzer. XRD pattern confirms the crystalline nature of the biosynthesized nanoparticles. The phytoconstituents involved in the reduction and stabilization of nanoparticles have been identified using FTIR spectra. The phytosynthesized AuNPs showed effective antioxidant, antibacterial and catalytic reduction activities. Furthermore, they have inhibited H1229 and MCF‐7 cancer cell lines proliferation in a dose‐dependent manner. These results have supported that D. kotschyi leaf extract was very efficient for the synthesis of AuNPs, and synthesized NPs showed enhanced biological activities which make them suitable for biomedical applications. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 621–630, 2019.